Central corneal thickness distribution study among Beninese patients - LAWANI, Rafiou; AYENA, Didier; SOUNOUVOU, Ignace (My University, 2015)
PURPOSE / AIM. The purpose of this study was to describe the central corneal thickness (CCT) distribution in Beninese population and determine its correlations with age, gender, intraocular pressure (IOP) and refraction. METHODS. A prospective study was conducted at military teaching hospital of Cotonou on glaucomatous and non glaucomatous patients after the informed consent. We collected epidemiological and demographic data, status of glaucomatous under treatment or not, refraction, IOP and CCT measurements. Data were analyzed using SPSS 17 with statistical threshold of 5%. RESULTS. A total of 530 patients were recruited. They consisted of 235 men and 295 women. The average age was 41.86±16 years old. The mean IOP was 16.01± 4.65 mm Hg, CCT average was 533±38 microns. There are afterbivariate analysis of the CCT with sex, a significant difference between men and women (530±37µm for men against 537±39 µm for women p = 0.01). The CCT decreases with age ranging from 560 ±50.85 µm between 10 and 19 years to 514.52 ±31 µm for 70 years and over, and a strong correlation was observed between IOP and CCT. CONCLUSION. The CCT is thinner in Beninese patients especially in men. CCT decreases with age and is significantly correlated with IOP.
Keywords: Glaucoma; Pachymetry; Central corneal; thickness; IOP; Benin.